Synthesis, Characterization, and Anticancer Activity of 3-Chlorothiophene-2-carboxylic Acid Transition Metal Complexes - Baiquan Hu; Qianqian Kang; Xianggao Meng; Hao Yin; Xingzhi Yang; Yanting Yang; Mei Luo (Inorganics)
In this study, 3-chlorothiophene-2-carboxylic acid (HL) was used as a main ligand to successfully synthesize four novel complexes: [Cu(L)2(Py)2(OH2)2] (1), [Co(L)2(Py)2(OH2)2] (2) (Py = pyridine), [{Ni(L)2(OH2)4}2{Ni(L)(OH2)5}]L•5H2O (3), and [{Co(L)2(OH2)4}2{Co(L)(OH2)5}]L•5H2O (4). All four compounds were identified by elemental analysis and ESI mass spectrometry, and subsequently characterized by IR spectroscopy, UV-visible diffuse reflectance spectroscopy, electron paramagnetic resonance spectroscopy, thermogravimetric analysis, single-crystal X-ray crystallography, and cyclic voltammetry. X-ray analyses revealed that complexes 1 and 2 exhibit a centrosymmetric pseudo-octahedral coordination geometry; the copper (II) and cobalt (II) metal ions, respectively, are located at the crystallographic center of inversion. The coordination sphere of the copper (II) complex is axially elongated in accordance with the Jahn–Teller effect. Intriguingly, for charge neutrality, compounds 3 and 4 crystallized as three independent mononuclear octahedrally coordinated metal centers, which are two <semantics>[ML2(OH2)4]</semantics> complex molecules and one <semantics>[ML(OH2)5]+</semantics> complex cation (M = <semantics>NiII</semantics> and <semantics>CoII</semantics>, respectively), with the ligand anion <semantics>L−</semantics> serving as the counter ion. The anticancer activities of these complexes were systematically assessed on human leukemia K562 cells, lung cancer A549 cells, liver cancer HepG2 cells, breast cancer MDA-MB-231 cells, and colon cancer SW480 cells. Among them, complex 4 shows significant inhibitory effects on leukemia K562 cells and colon cancer SW480 cells.